Determine the impact of wages on the rate of economically active people in Sinaloa from 2012 to 2023 using an econometric model - Gálvez-Rodríguez, Andrés; López-López, José-de-Jesús (Technium Social Sciences Journal, 2025)
The study examined the impact of the minimum wage on the participation of the economically active population (EAP) in Sinaloa between 2012 and 2023, using a linear regression model to analyse its relationship with variables such as GDP, inflation, interest rates and foreign direct investment. The findings revealed that the minimum wage has a positive and significant effect on labour participation, with a coefficient of 0.0147 (p=0.0023), while GDP also showed a positive influence, although other macroeconomic variables were not statistically significant. The model obtained an adjusted R² of 93.9%, highlighting its explanatory power, although factors such as inflation and foreign direct investment were not determinant, possibly due to the regional context and local economic structure. Limitations such as a 12-year observation period and the exclusion of variables such as educational level or gender were noted. In conclusion, the minimum wage is a key tool to encourage labour participation, but its effectiveness is conditional on the balance with economic growth, recommending sustainable wage policies, promotion of regional development and broader and longitudinal studies to better understand labour dynamics.